ANALISIS SIKAP KONSUMEN, KONTROL PERILAKU MENGENAI LABEL HALAL PADA PRODUK (STUDI KASUS: MAHASISWA PTS DI KOTAMADYA PONTIANAK) - Mardiyati Mardiyati; Hijrah Wahyudi (Jurnal Ekonomi STIEP, 2020)
The purpose of this research is to know the college student’s attitude and behaviour control of halal label in product ; to discover how much this issue affect them. This analysis is done by using descriptive analysis in order to answer the research. This research is done to 200 college students ( from STIE Indonesia Pontianak, and STIE Pontianak). Result of the research concludes that majority of responden agree of label halal on product, behaviour control of respondens are agree too and the ranking of buying halal item start from food, medicine, cosmetic and cloth.